An exploration on ethical norms followed by healthcare professionals - SHREE, MS. KC RAJA; MS. BHAKIYALAKSHMI M, (The journal of contemporary issues in business and government, 2020)
Ethics is characterized as the moral standards that regulate the actions of a person or individual. Healthcare professionals are people who provide health care services and treatment based on their knowledge and experience. Medical ethics is the relevant subject of ethics that analyzes scientific medicinal drugs and associated medical research. Medical ethics is primarily based on the set of values that an expert can talk to in case of misunderstanding or conflict. Ethical Norms followed by Healthcare professionals is influenced by various factors such as Behaviour, Knowledge and Working environment. This study focuses on the various ethical factors influencing health care professionals. This study is conducted to find out the ethical norms followed by the healthcare professionals and to find out the determinants of ethical norms followed by Healthcare Professionals. The conclusion of the study shows that among the factors behaviour, knowledge and working environment behaviour factor have a positive linear relationship and innovation towards Ethical norms.